EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KACANG TANAH (ARACHIS HYPOGAEA L.) DI KECAMATAN TABONGO KABUPATEN GORONTALO - Yusuf, Abdul Muin M.; Azis, Muhammad Arief; Rahim, Yunnita; Rahman, Rival (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
This study aims to determine the land suitability class and limiting factors for the growth of peanut plants. This study was conducted from February to June 2024 in Tabongo District, Gorontalo Regency. This study uses a matching method or matching of the characteristics of the Tabongo District land with the criteria for the suitability of peanut plant land to produce actual and potential land suitability classes. The results of the analysis show that Tabongo District has two Actual land suitability classes for peanut plants, namely class S3 (Marginally suitable) with subclass S3 (nr, na) spread across land unit 1 covering an area of ​​48.75 ha (4.68%), S3 (rc, na) in land unit 2 covering an area of ​​176.31 ha (16.92%) and S3 (na, eh) in land units 3 and 4 covering an area of ​​778.38 ha (74.7%) and N (Not suitable) with subclass N (eh, lp) spread across land unit 5 covering an area of ​​38.61 ha (3.7%). Each subclass has limiting factors including Nr (nutrient retention pH-H2O), na (Available Nutrients K2O), rc (effective depth), eh (slope and erosion hazard), and lp (rock and rock outcrops on the surface). After the improvements were made, Tabongo District had three potential land suitability classes for peanut plants, namely, S2 (Quite suitable) covering an area of ​​48.75 ha (4.68%), S3 (Marginally suitable) covering an area of ​​954.69 ha (91.61%) and N (Not suitable) covering an area of ​​38.61 ha (3.71%) of the total area of ​​the research area.